Effect of Limb Dominance on Chronic Ankle Instability: Does It Matter? - Dakhode, Shubham Yashwant; Kim, Woo Sub; Lee, Seung Yeol (International Journal of Sports Medicine, 2024)
Our study aimed to examine preoperative differences in strength and balance between dominant foot (DF) and nondominant foot (non-DF) of individuals undergoing ligament stabilization surgery in the general population. Patients with records of preoperative evaluation, including isokinetic dynamometric strength evaluation, Y-balance test (YBT), and Foot and Ankle Outcome Score (FAOS), were included in the study. The DF was the preferred leg for accurately kicking a ball through a goal. Statistical analysis determined the differences between DF and non-DF and the correlations between muscle strength, balance, and FAOS. There was no statistically significant difference between DF and non-DF regarding evertor and invertor muscle strength (p=0.082–0.951). The YBT revealed no significant difference between the two groups (p=0.082–0.951). There was a significant correlation between the evertor peak torque and total work deficits at 30°/s (p=0.022), as well as the evertor peak torque deficit at 120°/s (p=0.048). No significant differences in muscle strength and balance were found between DF and non-DF in nonathletes with chronic ankle instability. Peroneal muscle strength deficit was associated with functional impairment. Tailored interventions are needed to address limb dominance and muscle strength deficits in CAI management.
Keywords: dominant foot; muscle strength; balance; foot and ankle outcome score